BODIPY Dye, the Most Versatile Fluorophore Ever?. Issue 1 (11th January 2016) - Bañuelos, Jorge
Abstract: BODIPY laser dyes constitute a fascinating topic of research in modern photochemistry due to the large variety of options its chromophore offers, which is ready available for a multitude of synthetic routes. Indeed, in the literature one can find a huge battery of compounds based on the indacene core. The possibility of modulating the spectroscopic properties or inducing new photophysical processes by the substitution pattern of the BODIPY dyes has boosted the number of scientific and technological applications for these fluorophores. Along the following lines, I will overview the main results achieved in our laboratory with BODIPYs oriented to optoelectronic as well to biophotonic applications, stressing the more relevant photophysical issues to be considered in the design of a tailor‐made BODIPY for a certain application and pointing out some of the remaining challenges. Abstract : BODIPY dye, the most versatile fluorophore ever? The BODIPY chromophore is a versatile platform for post‐functionalization which allows fine tuning of its photophysical signatures. Thus, and after a rational molecular design, tailor‐made fluorophores can be developed for the target application field, ranging from optoelectronics (such as tunable laser dyes or molecular antennas) to biophotonics (luminescence sensors, switches and probes, or singlet‐oxygen photosensitizers).